The Impact of the Sustainable Financing Ratio on Credit Risk and Profitability of KBMI IV Banks in Indonesia for the Period 2015 - 2025 (West Science Journal Economic and Entrepreneurship, 2026)
This study analyzes the impact of the Sustainable Financing Ratio (SFR) on the credit risk and profitability of KBMI IV banks in Indonesia during the 2015–2025 period. Credit risk is proxied by the Non-Performing Loan (NPL) ratio, while profitability is proxied by Return on Assets (ROA). The Capital Adequacy Ratio (CAR), Loan-to-Deposit Ratio (LDR), and Bank Size are used as control variables. The sample comprises Bank Mandiri, Bank Negara Indonesia, Bank Rakyat Indonesia, and Bank Central Asia, yielding 44 observations. Secondary data were obtained from annual reports, sustainability reports, financial statements, and publications by the Financial Services Authority (OJK). The analysis employs panel data regression using the Random Effect Model (REM), Nerlove transformation, and bank-level clustered standard errors. The results indicate that SFR has a positive and significant effect on NPLs, with a coefficient of 0.0439874 and a p-value of 0.0000821. Conversely, SFR has a negative and significant effect on ROA, with a coefficient of −0.0139732 and a p-value of 0.0005. Collectively, SFR, CAR, LDR, and Bank Size significantly influence both NPLs and ROA. These findings suggest that the increase in the proportion of sustainable financing among KBMI IV banks during the observation period is associated with higher credit risk and lower profitability. Therefore, the expansion of sustainable financing must be accompanied by strengthened risk management, monitoring of credit quality, and attention to the banks’ efficiency and financial performance.